2019
DOI: 10.1002/aur.2130
|View full text |Cite
|
Sign up to set email alerts
|

Egocentric biases and atypical generosity in autistic individuals

Abstract: Individuals with autism spectrum conditions (ASCs) often experience difficulty and confusion in acknowledging others' perspectives and arguably exhibit egocentricity. However, whether this egocentricity necessarily results in selfish behavior during social situations remains a matter of debate. To study this relationship, we used computerized visuospatial perspective‐taking task (VPT) and social‐discounting task (SDT), derived from cognitive psychology and behavioral economics, and examined egocentric and othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
42
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 54 publications
7
42
3
Order By: Relevance
“…As both ToM and VPT-2 demand simultaneous representations of two differing viewpoints (mental states in ToM and visual states in VPT-2), ASC children, characterized by ToM deficits, also have difficulty in VPT-2 tasks, suggesting that an abnormality in decoupling representations from reality and inhibiting their own perspective could account for ASC children’s poor VPT-2 performance in the present study and the well-documented ToM deficits in previous studies (Tin et al, 2018; White et al, 2009). However, it is also worth noting that lower performance and higher egocentric bias on VPT and ToM do not mean that ASC individuals are totally self-centered or selfish, for some studies have suggested that ASC children could afford comfort to others and even showed more generosity than NT controls (Dunfield et al, 2019; Tei et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As both ToM and VPT-2 demand simultaneous representations of two differing viewpoints (mental states in ToM and visual states in VPT-2), ASC children, characterized by ToM deficits, also have difficulty in VPT-2 tasks, suggesting that an abnormality in decoupling representations from reality and inhibiting their own perspective could account for ASC children’s poor VPT-2 performance in the present study and the well-documented ToM deficits in previous studies (Tin et al, 2018; White et al, 2009). However, it is also worth noting that lower performance and higher egocentric bias on VPT and ToM do not mean that ASC individuals are totally self-centered or selfish, for some studies have suggested that ASC children could afford comfort to others and even showed more generosity than NT controls (Dunfield et al, 2019; Tei et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, level-2 visual perspective-taking (VPT-2), acquired around 5 years of age, takes a step further to enable children to determine how the same object could appear differently from another person’s point of view (Flavell, 1977; Gzesh & Surber, 1985). The majority of studies suggest that while VPT-1 is intact in people with autism spectrum conditions (ASCs; Tei et al, 2019; Warreyn et al, 2005), the VPT-2 is impaired or delayed in this group (Hamilton et al, 2009; Pearson et al, 2013; Yirmiya et al, 1994). And the difficulty in perspective-taking may place one at a social disadvantage, struggling to align with other people’s perspectives and recognize their feelings, intentions, or beliefs (Hamilton et al, 2009; Wallace et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the ability to distinguish the behaviors of in‐group and out‐group members is considered to have developed through evolution (Balliet et al, ; Baumgartner, Schiller, Rieskamp, et al, ). Patients with various psychiatric disorders, such as ASD and schizophrenia, have a reduced capacity to read and adapt to prevalent group norms and practices and often fail to trust and cooperate even with individuals who are close to them (De Dreu & Kret, ; Fujino, Takahashi, et al, ; King‐Casas et al, ; Tei, Fujino, et al, ). Therefore, these patients have difficulty forming and maintaining social bonds and suffer from social exclusion and isolation (De Dreu & Kret, ).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, impairments in such group psychology undermine social inclusion and fitting in (Balliet et al, ; De Dreu & Kret, ). Individuals who chronically suffer from these impairments, including those diagnosed with autism spectrum disorder (ASD), schizophrenia, and borderline personality disorder, risk a lack of social support and have a reduced well‐being (De Dreu & Kret, ; King‐Casas et al, ; Tei et al, ). Thus, an improved understanding of intergroup trust bias can provide significant insights into social cognitive functioning and its impairments in psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the abundance of studies on increased cognitive biases in ASD, using e.g. false belief or social discounting tasks (Begeer et al, 2012;Frith & de Vignemont, 2005 for a review; Nijhof et al, 2020;Tei et al, 2019), biases in the emotional domain seem to have gotten less attention over the years. However, affective social competences are often a major problem for individuals with ASD, and there is still a wide debate which components of social cognition are indeed impaired in this disorder (Deschrijver & Palmer, 2020 for a recent review; Dziobek et al, 2008;Mazza et al, 2014).…”
Section: Introductionmentioning
confidence: 99%